O esclarecimento Kantiano - Souza, Paola Nunes de (2019)
This research aims to investigate some aspects related to the concept of Aufklärung present in the writings of Immanuel Kant, from the analysis of the Enlightenment process developed by the philosopher. From the observation of Kantian works, we see that this process presupposes as necessary the use of understanding, autonomy, self-thinking and freedom on the part of the subjects involved, thus presenting a unique correlation with Kant's ethics, and also articulate with fundamental political and educational aspects. In this sense, in order to understand Aufklärung or the Kantian Enlightenment, this dissertation seeks, firstly, to analyze some historical aspects of this concept and also the context in which the question that moved the German Illustration about the term Aufklärung in 1783 arises. Subsequently, we seek to analyze more deeply the Kantian answer and also to observe the way the dialogue on the theme is built, from other questionings present in Kant's own critical philosophy. Finally, besides discussing some of the metacritical links that the Kantian discussion establishes with its historical time and its own philosophy, we try to think about the current concept of Enlightenment, from the reflection of contemporary theorists who thought about the Aufklärung process.